Where is the Rosin in this Picture? - Hercules Incorporated (1946 Hercules Advertisements, 1946)
Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Hercules Incorporated; Corporations; Naval stores; Advertising, Industrial; Gums and resins; Pine needles--Terpene content; Terpenes; Paper sizing; Varnish and varnishing